2006
DOI: 10.1134/s1063772906110011
|View full text |Cite
|
Sign up to set email alerts
|

Photometric and spectroscopic study of the Shakhbazian compact galaxy groups ShCG 254, ShCG 257, ShCG 351, and ShCG 371

Abstract: How to citeComplete issue More information about this article Journal's homepage in redalyc.org Scientific Information System Network of Scientific Journals from Latin America, the Caribbean, Spain and Portugal Non-profit academic project, developed under the open access initiative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23]. A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23].…”
Section: Observations and Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23]. A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23].…”
Section: Observations and Resultsmentioning
confidence: 97%
“…Spectral and photographic observations of a large number of ShCG groups have been made by Tiersch et al [14 and references therein] and Tovmassian et al [15][16][17][18][19][20][21][22][23]. It was shown that the majority of the candidate group members were galaxies with accordant radial velocities (usually < 1000 km s -1 ).…”
mentioning
confidence: 99%
“… Comparison between our spectroscopic size estimates of the SHK groups and those performed by Tovmassian et al (1999–2007) (plain dots), Tiersch et al (1994–2002) (diamonds) and Kirshner & Malumuth (1980) (asterisks)(upper panel). Similarly, in the lower panel, our size estimates of the HCGs are compared with those performed by Hickson (1982) and Hickson et al (1992).…”
Section: Group Propertiesmentioning
confidence: 98%
“…Our size estimates are consistent with the HCGs sizes for ∼50 per cent of the sample . For the SHK sample, where sizes calculated according to photometric criteria are not available in literature, we compare with the virial radii of the groups measured by Tovmassian et al (1999–2007) and Tiersch et al (1994–2002). According to Tovmassian et al (2005c), the virial radii generally do not exceed ≈ 160 kpc, while the mean mass‐weighted radial velocity dispersion is 330 ± 170 km s −1 (Tovmassian et al 2007), ranging from 88.5 to 667.1 km s −1 , thus implying dynamical crossing times varying from 2.7 × 10 7 to 1.9 × 10 8 yr (Tovmassian et al 2005c, 2007), on an average shorter than what found for the HCGs ≈ 2.1 × 10 8 yr (Hickson et al 1992).…”
Section: Group Propertiesmentioning
confidence: 99%
See 1 more Smart Citation